Targeting pronunciation the intonation, sounds, and rhythm of American English - Miller, Sue F. (Houghton Mifflin, 2000)
This comprehensive pronunciation text encourages students to set their own learning agenda and practice in and outside the classroom. The text uses a communicative approach and clear explanations to build pronunciation awareness and provides extensive practice for all aspects of pronunciation.